Exploring the Awareness and Acceptability of Philippine English among Language Studies Students in a State College - Fajardo, Dan Fereth (Masyarakat Linguistik Indonesia Universitas Andalas, 2025)
This study explores the awareness and acceptability of Philippine English (PhilE) among language studies students at a state college in the Philippines. While Philippine English has achieved recognition as a legitimate English variety in academic, professional, and media domains, its acceptance, especially in educational settings, remains uneven due to entrenched native-speaker norms. Using an explanatory sequential mixed methods design, the study first employed a validated survey instrument to gather quantitative data from ninety-seven (97) respondents. Descriptive statistics and Pearson product-moment correlation were used to measure levels of awareness and acceptability, and the relationship between them. This was followed by semi-structured interviews with six (6) participants. Findings revealed that students were generally aware of the meaning, features, and uses of PhilE, with highest awareness scores for grammatical and pronunciation features and usage in digital media. However, acceptance of PhilE grammatical and lexical items remained limited, especially in formal contexts. A statistically significant but inverse correlation (r = –.995, p < .001) was found between awareness and acceptability—suggesting that greater knowledge may reinforce prestige bias rather than dismantle it. Three key factors influencing awareness and acceptability were identified: (1) educational exposure and curricular influence, (2) digital media and online representation, and (3) peer and instructor influence. The findings highlight the urgent need for a critical pedagogical shift which not only raises awareness of local English varieties but also fosters linguistic pride and legitimacy. Implications point to the inclusion of PhilE in curricula, teacher training, and institutional policy as necessary steps toward equitable and context-sensitive English language education in the Philippines.